We Became "Therapists Without a License”- A Phenomenological Study of Care Managers Working with Older Adults during a Pandemic (Journal of Advanced Research in Social Sciences, 2024)
The study sought to understand the lived experience of Care managers employed by aging networks and their role during the COVID-19 pandemic in helping older adults living in the community maintain their independence. The COVID-19 pandemic propelled care managers to navigate new challenges by developing innovative ways of providing services to older adults. Purposive sampling was used (n=15) to recruit Care Managers to participate in focus groups. Qualitative data were transcribed and analyzed using NVivo-12 software. Five themes emerged from the data: Older Adults with Mental Health, Emotional Distress, Challenges Accessing Resources, A Shift to the Care Management Role, and Support from Management. The essence of the experience was that care managers who work in the aging network play a significant role in the lives of older adults living in the community by providing community-based long-term services and support. During COVID-19, the role of the care managers was amplified, with care managers providing psychological and emotional support to older adults due to the shortage of mental health providers. Care Managers worked with limited resources to identify innovative ways of providing services during this public health crisis.